Comparison of long-term complications of using amplatzer ductal occluder and ventricular septal defect occluder for transcatheter ventricular septal defect closure - Mehdi Ghaderian; Negin Salemi (Heart Views, 2021)
Background: Ventricular Septal Defect (VSD) is the most common type of congenital heart disease and perimembranous type is the commonest form of these defects. Trans-catheter management of these defects is a challenging procedure. Objectives: The purpose of this study was to compare of Trans-catheter closure of perimembranous ventricular septal defect (PMVSD) using Amplatzer Ductal Occluder (ADO) and VSD occluder and their complications and follow-up. Patients and Methods: Between 2013 and April 2019, 69 patients underwent percutaneous closure of PMVSD using ADO (29 patients) and VSD occluder (40 patients). After obtaining the size of VSD from the ventriculogram at least 2 mm larger than the orifice diameter of VSD at the right ventricular side was chosen. The devices were positioned after verification of the proper device position by echocardiography, aortogram and left ventriculography. Results: The mean age of patients were 9.07 ± 7.73 years, mean weight 26.12 ±16.25 kg. The mean defect size of the right ventricular orifice and device sizes were 5.54 ± 1.83 mm 7.72 ± 1.94 mm respectively. Small residual shunts were seen at the completion of the procedure, but they disappeared during follow-up in all but one patient. Two patients had mild AI before the procedure in ADO group that disappeared during the follow-up. The mean follow-up period was 3.3 ± 1.7 years (range 1 to 6 years). Complete atrioventricular block (CAVB) was seen in one patient (VSD occluder) during the procedure that disappeared after the retrieval of the device. Major complication or death was not observed in our study. Conclusions: Trans-catheter closures of PMVSD with ADO or VSD occluder had similar effects in these patients and are safe and effective treatment associated with excellent success and closure rates. Long-term follow-up in a large number of patients is warranted.